PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN, NILAI, KEPERCAYAAN DAN LOYALITAS PELANGGAN RUMAH TANGGA PADA PERUSAHAAN DAERAH AIR MINUM KOTA KENDARI - Kadir, Abdul; Basri, Muhammad; Rodi, Rodi (Universitas Halu Oleo, 2018)
ABSTRACTThis study aims to determine the effect of service quality on customer loyalty mediated by Customer satisfaction and customer value addition, it also examines, the effect of service quality on customer satisfaction, which is mediated by the effect of customer value and customer satisfaction and customer value on customer loyalty mediated by trust. The population in this study are household customers in Kendari who use the services of PDAM for 17,607 households spread are over 10 (ten) districts. The samples in this study are 391 household customers are taken with a precision of 5 % Data Collection techniques utilities questionnaire. Data are analyzed by using. Structural Equation Modelling (SEM) with the help of the program, some of the important findings in this study are : (1) better service improvement of Kendari Regional causes trust, (2) customer loyalty improvement is also achievable of the provided service is able to enhance customer value. Besides, this research also proves that trust has a mediating role between satisfaction and loyalty of are customers as well as between customer value and loyalty. Keywords : service quality, customer satisfaction, customer value, customer trust and customer loyalty.